TINJAUAN YURIDIS TERHADAP PRAKTIK TUKANG GIGI DI JAKARTA SELATAN - , Ari Rabiwaldhy, Dwi Haryati, SH, MH ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the implementation of the practice of dental artisans in South Jakarta, knowing the supervision of dental artisans in South Jakarta under the Regulation of the Minister of Health of the Republic of Indonesia Number 339/Menkes/Per/V/1989, as well as the response / response to the revocation of Junior gear Regulation of the Minister of Health of the Republic of Indonesia Number 339/Menkes/Per/V/1989 about Junior dental work. This research is the nature dekriptif, presents the results of observations, and then examine the various provisions related and relavan, using the empirical approach to problems and sociological / field. The data used is more emphasis on data sekunder, while the primary data is more suppor Data analysis of empirical legal research with the normative approach according to the legislation (Statutory Conceptual) and conceptual approaches (Conceptual Conseptual). From the results of these studies are presented in a qualitative way. The data obtained in this study will be grouped and disistimatisasi. The data was then analyzed qualitatively disistimatisasi. Primary data obtained will then be evaluated with the legislation governing the work of dental artisan. Based on that evaluation will be obtained by way of inductive inference. The results showed that: 1. In the implementation of dental practices in South Jakarta builders do not meet the requirements of the provisions mentioned in the Minister of Health No. 339/Menkes/Per/V/1989 of Junior Dental Work and Decision No. DG MOH Yanmed 234/Yanmed/KG/5/1991, about Registration Procedures and Junior Dental Work Permit. 2. Supervision of dental handyman license in South Jakarta by Jakarta City Health Department is never done. 3. There is a tendency of resistance to the implementation of the Regulation of the Minister of Health No. 1871/Menkes/PER/IX/2011 on Revocation of Regulation of the Minister of Health No. 339/MENKES/PER/V/1989 About Junior Dental Work.